MEDIA KOMIK STRIP DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAGI PEMBELAJAR BIPA LEVEL 3 - Pamorria, Virdha (Journal Educational of Indonesia Language, 2024)
This study was made with the aim of describing the use of comic strip media in learning Indonesian for Foreign Speakers (BIPA), especially for foreign students from Thailand. There are many reasons why foreign students who take part in BIPA learning do not really understand the material provided, one of which is the lack of media to convey the material as well as to attract the interest and enthusiasm of students. Therefore, to arouse the enthusiasm and interest of foreign students is to use efficient and entertaining learning media, one of which is comic strip media. This study uses qualitative research methods and analytical techniques using qualitative descriptive. The results of this study found the benefits of using comic strip media for foreign students from Thailand including (1) learning is more active and interesting, (2) strengthening students' memory of Indonesian vocabulary, (3) students being more communicative in speaking, (4) learning materials. teach to innovate to be more creative, (5) a means of delivering Indonesian language and vocabulary, (6) students are entertained so that learning objectives are achieved.  Keywords: comic strips, learning media, BIPA.